Opportunities and challenges for improved forage seed market development: Insights from Kenya and other East African countries - Florez H, Fernando; Karimi, Peggy; Junca, John Jairo; Triana, Natalia; Burkart, Stefan (2024)
In East Africa, forage constitutes a primary food source for dairy cattle. While local forage varieties are preferred by dairy farmers, there has been an increase in the adoption of improved forages in recent years, including forage hybrids of the species Urochloa. The aim of this study was to analyze the dynamics of the improved forage seed market in Kenya and other East African countries within the last decade. Additionally, it seeks to construct a forward-looking analysis of the market's projected evolution over the next decade, and to identify the challenges and prospects for improvement. For this purpose, we conducted 46 key informant interviews in 2022/2023 with the main stakeholders of the forage seed system, i.e., seed companies, public entities, research institutions, and farmers. The results show a sustained growth of the improved forage seed market in recent years. The main challenges for further growth are high seed prices, regulatory difficulties, and limited awareness and knowledge among producers regarding improved forage varieties and how to correctly use them. Our findings unveil a virtuous circle that holds potential to scale the adoption of improved forages in the region and address identified challenges: Research institutions are committed to the improvement of existing varieties and the introduction of novel materials through their breeding and seed selection initiatives. Seed companies are eager to amplify their seed supply. Governments and developmental entities express strong interest in providing support in the adoption process of improved forages. Collaborative alliances between producer associations and seed companies are on the horizon, aimed at distributing seeds to farmers at more accessible prices. Lastly, dairy farmers exhibit keen interest in improved forages due to their potential to elevate milk production, optimize cattle farming land use, and for climate change adaptation.